Pornography Addiction Among 7th Grade Students in the Urban Community: Mixed-Method Research - Abadi, Dinda Putri; Muslihati; Yuliati Hotifah (Bisma The Journal of Counseling, 2025)
The advancement of information technology has significantly accelerated the dissemination of information, including harmful content such as pornography. This phenomenon raises concerns about the potential for pornography addiction among adolescents with unrestricted access to digital media. This study aims to analyze the level of pornography addiction tendencies among junior high school students and to explore the role of guidance and counseling services in addressing this issue. A mixed-methods approach was employed using an exploratory sequential design. Quantitative data were collected through a survey assessing the level of pornography addiction, while qualitative data were obtained through focus group discussions (FGD) with school counselors to examine implemented strategies and encountered challenges. Instruments included a pornography addiction scale and structured interview guidelines. Quantitative findings reveal that the majority of students (93.2%) fall into the low addiction tendency category, while 6.8% are in the moderate category. Qualitative results indicate that pornography addiction is driven by uncontrolled technological access, lack of supervision, and negative social influences. Although preventive efforts have been initiated through counseling services, their effectiveness remains limited due to insufficient support and inadequate facilities. The study recommends the development of educational media focused on enhancing adolescents’ self-control as a strategic intervention to prevent pornography addiction in secondary education contexts.